Chemical Vapour Deposition of Graphene for Durable Anticorrosive Coating on Copper - Ji, Dali (Nanomaterials (Basel), 2020)
Due to the excellent chemical inertness, graphene can be used as an anti-corrosive coating to protect metal surfaces. Here, we report the growth of graphene by using a chemical vapour deposition (CVD) process with ethanol as a carbon source. Surface and structural characterisations of CVD grown films suggest the formation of double-layer graphene. Electrochemical impedance spectroscopy has been used to study the anticorrosion behaviour of the CVD grown graphene layer. The observed corrosion rate of 8.08 × 10(−14) m/s for graphene-coated copper is 24 times lower than the value for pure copper which shows the potential of graphene as the anticorrosive layer. Furthermore, we observed no significant changes in anticorrosive behaviour of the graphene coated copper samples stored in ambient environment for more than one year.